The Error Analysis of Google Translate and Bing Translator in Translating Indonesian Folklore - Jufriadi, Jufriadi; Asokawati, Amalia; Thayyib, Magfirah (Faculty of Education and Teacher Training of IAIN Palopo, 2022)
The objective of this research is to find out the lexical errors made by Google Translate and Bing Translator in translating Indonesian folklore